Characteristics of positive-interaction parenting style among primiparous teenage, optimal age, and advanced age mothers in Canada - Kim, Theresa H. M. (BMC Pediatr, 2018)
BACKGROUND: Positive-interaction parenting early in childhood is encouraged due to its association with behavioural development later in life. The objective of this study was to examine if the level of positive-interaction parenting style differs among teen, optimal age, and advanced age mothers in Canada, and to identify the characteristics associated with positive-interaction parenting style separately for each age group. METHODS: This was a cross-sectional secondary analysis of the National Longitudinal Survey of Children and Youth. First-time mothers with children 0–23 months were grouped into: teen (15–19 years, N = 53,409), optimal age (20–34 years, N = 790,960), and advanced age (35 years and older, N = 106,536). The outcome was positive-interaction parenting style (Parenting Practices Scale); maternal socio-demographics, health, social, and child characteristics were considered for backward stepwise multiple linear regression modeling, stratified for each of the age groups. RESULTS: Teen, optimal age, and advanced age mothers reported similar levels of positive- interaction parenting style. Covariates differed across the three age groups. Among optimal age mothers, being an ever-landed immigrant, childcare use, and being devoted to religion were found to decrease positive-interaction parenting style, whereas, higher education was found to increase positive-interaction parenting style. Teen mothers were not found to have any characteristics uniquely associated with positive-interaction parenting. Among advanced age mothers, social support was uniquely associated with an increase in positive-interaction parenting. Very good/excellent health was found to be positively associated with parenting in teens but negatively associated with parenting in advanced age mothers. CONCLUSION: Characteristics associated with positive-interaction parenting varied among the three age groups. Findings may have public health implications through information dissemination to first-time mothers, clinicians, researchers, and public health facilities.